Production Inventory Models for Deteriorating Items with Stochastic Machine Unavailability Time, Lost Sales and Price-Dependent Demand - Gede Agus Widyadana; Hui Ming Wee (Institute of Research and Community Outreach - Petra Christian University, 2010)
The economic production quantity (EPQ) model is widely employed in reality and is also being intensively developed in the research area. This research tries to develop more realistic EPQ models for deteriorating items by considering stochastic machine unavailability time (uniformly and exponentially distributed) and price-dependent demand. Lost sales will occur when machine unavailability time is longer than the non production time. Since the closed form solution cannot be derived, we use Genetic Algorithm (GA) to solve the models. A numerical example and sensitivity analysis is shown to illustrate the models. The sensitivity analyses show that a management can use price policy to minimize the profit loss due to machine unavailability time under a price- dependent demand situation